Different life strategies of the three commercially exploited scallop species living under the same environmental conditions - Ezgeta-Balić, Daria; Peharda, Melita; Schöne, Bernd R.; Uvanović, Hana; Vrgoč, Nedo; Markulin, Krešimir; Radonić, Ivana; Denamiel, Cléa; Kovač, Žarko (Frontiers in Marine Science, 2022)
To understand the response of marine species to a changing environment, it is crucial to have deep insight into their main biological traits. This study used a multi-species approach to comparatively analyse the reproductive and growth strategies of three commercially important scallop species. Target taxa were larger sized Mediterranean scallop Pecten jacobeaus, and two smaller sized species Aequipecten opercularis and Flexopecten glaber. Specimens were collected at approximate monthly intervals from February 2017 to October 2018 from a commercial beam trawl in the northern Adriatic area (west coast of the Istria peninsula, 25-35 m depth). Three different complementary methods were applied to obtain comprehensive knowledge about the reproductive cycle including assessment of the gonadosomatic index (GSI), histological analysis of gonad tissue, and measuring oocyte size. Growth strategies of three target species were analyzed using high-resolution stable oxygen isotope data that were temporally aligned on sea water temperature data obtained by AdriSC ROMS model. Results indicate diverse strategies employed by these taxonomically related species exposed to the same environmental conditions. Pecten jacobaeus spawned in the late summer and early fall, while shell growth slowed down during warmer season. Aequipecten opercularis spawned in the winter and slowed down shell deposition process during the cold season. Spawning of F. glaber occurred during early to mid-summer and growth slowed down during warmer season. This study provides an important scientific baseline for sustainable management and future aquaculture attempts of scallops.